1995
DOI: 10.1093/genetics/139.1.189
|View full text |Cite
|
Sign up to set email alerts
|

Variation in sperm displacement and its association with accessory gland protein loci in Drosophila melanogaster.

Abstract: Genes that influence mating and/or fertilization success may be targets for strong natural selection. If females remate frequently relative to the duration of sperm storage and rate of sperm use, sperm displacement may be an important component of male reproductive success. Although it has long been known that mutant laboratory stocks of Drosophila differ in sperm displacement, the magnitude of the naturally occurring genetic variation in this character has not been systematically quantified. Here we report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(84 citation statements)
references
References 27 publications
5
79
0
Order By: Relevance
“…Previous studies that measured the proportion of progeny sired by alternative males in double mating experiments have suggested that the competitive ability of sperm varies among male genotypes [8]. In particular, bw D males have been shown to be poor sperm removers on the basis of the proportion of progeny they sire as second males (their P2 scores) [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that measured the proportion of progeny sired by alternative males in double mating experiments have suggested that the competitive ability of sperm varies among male genotypes [8]. In particular, bw D males have been shown to be poor sperm removers on the basis of the proportion of progeny they sire as second males (their P2 scores) [10].…”
Section: Resultsmentioning
confidence: 99%
“…Scores of sperm competition were obtained by setting up matings between 4-6-day-old virgin B3-09 females to same-aged dj-GFP males (which bear the CyO marker) followed by males from lines B3-09 or bw D . Sperm competition (P2) was measured from progeny counts [8] obtained from these matings. Progeny were scored for wing phenotype (wild type if sired by bw D or B3-09 males and curly if sired by dj-GFP males) about 15 days after oviposition began.…”
Section: Resultsmentioning
confidence: 99%
“…For example, females mated to transgenic males that lack specific seminal fluid proteins, show differences in post-mating transcript abundances, as compared to females mated to wildtype males with a full complement of seminal fluid proteins (McGraw et al 2004(McGraw et al , 2008Domanitskaya et al 2007;Gioti et al 2012). Additionally, polymorphisms in genes encoding seminal fluid proteins impact female post-mating responses and the male's reproductive success (Clark et al 1995;Prout and Clark 1996;Hughes 1997;Clark et al 2000;Fiumera et al 2005Fiumera et al , 2006; Greenspan and Clark 2011;Lüpold et al 2012;Zhang et al 2013). Thus, male seminal fluid proteins represent a major molecular component in the reproductive interactions that affect post-mating phenotypes in D. melanogaster.…”
mentioning
confidence: 99%
“…Embryos did not die due to excessive polyspermy, which is thought to be a risk for females copulating with multiple males with highly competitive sperm [119,120] (although some degree of polyspermy may be beneficial in birds [121,122]). The same sperm trait was positively associated both with a "defensive" role in fertilizing within-pair eggs and an "offensive" role in fertilizing extra-pair eggs [46,123], and a single sperm trait drove fertilization success [124]. All of these complexities are likely to weaken or obscure the relationship between sperm traits and fertilization success, because variation in fertilization success is explained by the other factors [14,88,89] or because selection on the sperm trait is non-linear.…”
Section: Simplifying Assumptions In the Simulationmentioning
confidence: 99%